Effects of an exercise intervention on maternal depression, anxiety, and fatigue: a systematic review and meta-analysis - Yu, Haoran; Mu, Qinglei; Lv, Xunjin; Chen, Shuainan; He, Hao (Frontiers in Psychology, 2024)
Background: Existing meta-analyses suggest that exercise intervention may play a crucial therapeutic role in improving maternal depression, anxiety and fatigue symptoms. However, the efficacy varies across different exercise content, duration, frequency, cycle, intensity, format and intervention period. Objective: Using meta-analysis to propose the best intervention program and examine the effect of exercise intervention on maternal depression, anxiety, and fatigue. Methods: Five databases (PubMed, Web of Science, Embase, Cochrane Library, CNKI) were searched from inception to June 2024, a total of 37 literatures were included. The methodological quality of the included literatures was assessed using the Cochrane Risk of Bias tool and the PEDro scale. When heterogeneity was high, we used random-effects models. Funnel plots were used to assess publication bias. Sensitivity analysis was used to verify the robustness of the combined results. Subgroup analysis was used to explore sources of heterogeneity. Results: Exercise has beneficial effects on the improvement of maternal depression[g=-0.71,95%CI(-0.93,-0.49),P=0.00], anxiety[g=-1.09,95%CI(-1.42,-0.76),P=0.00] and fatigue[g=-0.64,95%CI(-0.88,-0.40),P=0.00] symptoms. Postnatal interventions may be more effective than prenatal. Low-moderate intensity yoga with group + individual, 4-5times/week, 40-60min/time, duration 4-8weeks is most effective in improving depressive symptoms. Low-intensity yoga with group + individual, 4-5times/week, 40-60min/time, duration 4-8weeks is most effective for improving anxiety symptoms. Low-intensity Pilates with group, 1-2times/week, 40-60min/time, duration 4-8weeks is most effective for improving fatigue symptoms. Conclusions: This meta-analysis demonstrates the positive effect of exercise on improving maternal depression, anxiety and fatigue and suggests the best intervention program. Maternal perceptions that postpartum exercise is safer may account for the better outcomes of postpartum intervention. Further higher quality and large-scale trials are needed to substantiate our findings.